SOCIAL COGNITIVE REPRESENTATIONS OF VIOLENCE IN URBAN BRAZIL: VIOLENCE AS AN UNCONTROLLED FORCE - Pelosi, Ana Cristina (Revista da Anpoll, 2014)
The present paper reports on partial findings of a major research project entitled Interdisciplinary project on social cognitive representations in the conceptualization of violence in urban Brazilian centers. It aims at providing some insight into an embodied and social-culturally situated concept of representation – a social cognitive representation, as I understand it, by presenting both a theoretic-philosophical basis for this kind of concept as well as some preliminary findings of an analysis of focus groups talks about urban violence. The methodology is focused on discursive and cognitive aspects which emerge from and influence people’s verbal interactions. The qualitative analysis performed suggests, among others not discussed here, the emergence of two metaphors in participants’ talks: VIOLENCE IS A PRODUCT MANUFACTURED BY THE MEDIA and VIOLENCE IS A SPREADING CONTAGIOUS DISEASE. This appears to be due to the Media’s sensationalist trivialization of violence which results in violence being thought of as present anywhere and everywhere like an UNCONTROLLED FORCE. The trivialization of violence by the Media contributes to negative attitudes and feelings of lack of control, distrust, prejudice and hurt.